Gambaran Kepuasan Pasien Terhadap Pelayanan Kesehatan Gigi Dan Mulut Di Poli Gigi Puskesmas Cikuya Tahun 2023 - Rizaldy, Pingkan Imelliana; Alnur, Rony Darmawansyah (JURNAL PENDIDIKAN KESEHATAN, 2024)
Patient satisfaction is one of the primary indicators in the standards of a healthcare facility. Patient visits to the Cikuya Health Center fluctuated from 2019 to 2021. This may be due to internal and external factors. Internal factors include the services provided to patients, which may not meet their expectations, causing them to be reluctant to return for treatment. External factors include the improvement in community health levels. Creating patient satisfaction is not easy. One way to improve service quality is by measuring patient satisfaction levels. The aim of this study is to describe the level of patient satisfaction with dental and oral health services at the Cikuya Health Center dental clinic in 2023. This study was conducted at the Cikuya Health Center, with patient satisfaction measured based on five service dimensions: reliability, responsiveness, assurance, empathy, and tangibility. The method used in this study is descriptive quantitative, with a cross-sectional approach and non-probability sampling technique, namely accidental sampling, with a total sample of 177 respondents. The research instrument used was a questionnaire. The study results based on the five dimensions show the following patient satisfaction percentages with dental and oral health services: 1). Reliability dimension: 66% (116 respondents), 2). Responsiveness dimension: 74% (136 respondents), 3). Assurance dimension: 69% (122 respondents), 4). Empathy dimension: 68% (120 respondents), 5). Tangibility dimension: 64% (113 respondents). Overall, by combining the five dimensions, 158 (89%) of respondents stated they were satisfied with the dental and oral health services at the Cikuya Health Center dental clinic. It is recommended to improve services in the areas of reliability, responsiveness, and assurance, while maintaining services in the areas of empathy and tangibility